LEGISLATIVE CHANGES IN LEGAL REGULATION OF RIGHTS IN OFFICIAL WORKS IN ACCORDANCE WITH INTERNATIONAL LEGAL NORMS - Філик, Наталія Володимирівна; Грабовська, Ганна Миронівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: in the article the authors research changes in the legal regulation of rights in official works. Methods: classification of international instruments in the field of space law. Discussion: the authors emphasize the differences in regulation of the rights in official works and offer their recommendations for their removal. The authors agree with the scientists about the need for making amendments to labour legislation in order to properly regulate the rights in official works. Separately, attention is paid to the order of registration of labour relations with the employee as the author of official works.